(untitled) (Current Horticulture, 2024)
This study investigated the effects of boiling, drying, and ensiling on linamarin content, protein content, and mineral composition of cassava (Manihot esculenta Crantz) leaves. The drying was found effective method for reducing linamarin content in most genotypes. Boiling had variable effects, with some genotypes showing similar or slightly lower linamarin levels compared to fresh leaves. Ensiling significantly reduced linamarin content after 7 days, with the reduction remaining stable up to 20 days, indicating its effectiveness in reducing cyanogenic compounds. However, genotypes, H 1687 and Malayan 4, showed a decrease in protein content during ensilage, suggesting potential nutritional changes. The study also observed dynamic changes in mineral composition of cassava leaves, with copper, zinc, iron, and manganese varying over time. These findings highlight the impact of different processing methods on nutritional quality of cassava leaves, emphasizing the need to consider these factors when using cassava leaves as animal feed.